Self-healing polyurethane elastomer material based on dynamic reversible covalent bonds, preparation method of self-healing polyurethane elastomer material and seamless telescopic structure based on self-healing polyurethane elastomer material
By using dynamic reversible covalent bonds of self-healing polyurethane elastomer material and seamless telescopic structure design in the bridge expansion device, the problems of aging and insufficient splicing strength of existing devices are solved, and a bridge expansion device with high durability and self-healing function is achieved.
Patent Information
- Application Number
- CN202411983712.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The existing bridge expansion devices have problems such as aging material, insufficient splicing strength and high maintenance costs, making it difficult to maintain long-term stability in complex temperature and humidity environments.
The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds is adopted to realize the self-healing function of the material through the fracture and recombination of dynamic reversible covalent bonds, and a seamless telescopic structure is designed to enhance the mechanical strength and sealing of the splicing site.
It achieves excellent durability and self-healing ability of the material, extends the service life of the device, and avoids the problems of stress concentration and seal failure under traditional splicing methods.
Smart Images

Figure CN119899356A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of bridge telescopic structures, and in particular relates to a self-healing polyurethane elastomer material based on dynamic reversible covalent bonds, a preparation method and a seamless telescopic structure based on the material. Background Art
[0002] Bridge expansion joints are important structural components to ensure the normal operation of bridges. Their main function is to absorb and adjust the deformation of bridges caused by temperature changes, vehicle loads, and concrete shrinkage. However, existing mainstream expansion joints such as comb plate type, rubber strip type, and modular expansion joints generally have problems such as material aging, insufficient splicing strength, and high maintenance costs. The core materials of these devices are usually metal or rubber. During long-term use, they are easily affected by fatigue loads, high and low temperature cycles, and external environmental corrosion, and are prone to cracks, aging, and even fractures, which seriously affect the service life and structural safety.
[0003] In addition, the joints of traditional expansion joints are usually mechanically connected or chemically bonded, which can easily become weak links due to stress concentration. Under long-term loads and environmental stresses, the joint interface is prone to cracking, delamination or sealing failure, leading to the intrusion of external media such as rainwater and mud, which not only reduces the functionality of the device, but may also cause damage to the internal structure of the bridge. At the same time, due to the limitations of material properties and design methods, traditional splicing structures are difficult to maintain long-term stability in complex temperature and humidity environments.
[0004] The repair and maintenance of existing telescopic devices are also significantly difficult. Once the device is damaged, it is often necessary to replace the entire component to solve the problem, resulting in a complex and time-consuming construction process, long traffic interruption time, and high economic costs. In addition, most existing repair materials lack self-healing capabilities, making it difficult to effectively repair local problems such as cracks and fatigue damage.
[0005] To this end, developing a new type of splicing material and structural solution with self-healing function to improve the service life and performance of the telescopic device has become a technical problem that needs to be urgently solved in the field of bridge engineering. Summary of the invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a self-healing polyurethane elastomer material based on dynamic reversible covalent bonds, a preparation method and a seamless telescopic structure based on the material. The self-healing polyurethane elastomer material not only has excellent durability, but also can effectively repair cracks and damage through a self-healing mechanism; and the bridge telescopic structure based on the material adopts a seamless structural design, which enhances the mechanical strength and sealing of the splicing parts, and avoids the stress concentration and sealing failure problems that are prone to occur in traditional splicing methods.
[0007] Technical solution: The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds of the present invention includes the following raw materials by weight: 30-40 parts of diphenylmethane diisocyanate, 20-30 parts of fluorine-containing polyether polyol, 10-15 parts of polyethylene adipate diol, 5-10 parts of 4,4'-diaminodicyclohexylmethane chain extender, 3-6 parts of dynamic reversible bond monomer containing acylhydrazone bond functionalized small molecules, 2-4 parts of disulfide, 10-20 parts of silane-modified EPDM rubber particles, 1.5-4.5 parts of nano-filler material, 1-2 parts of triphenylphosphine, 0.1-0.3 parts of dibutyltin dilaurate, 0.1-0.2 parts of stabilizer, and 0.2-0.5 parts of silicone enhancer.
[0008] The self-healing polyurethane elastomer material of the dynamic reversible covalent bond of the present invention not only has excellent durability, but also can effectively repair cracks and damage through a self-healing mechanism, greatly extending the service life of the device. Specifically, based on fluorinated polyether polyols, polyethylene adipate diols and diphenylmethane diisocyanate, the hydroxyl groups in the fluorinated polyether polyols and polyethylene adipate diols act as nucleophilic reagents and undergo nucleophilic addition reactions with the isocyanate groups of diphenylmethane diisocyanate to form carbamate bonds (-NH-COO-). The main driving force of this reaction comes from the high electronegativity of the isocyanate group and the nucleophilicity of the hydroxyl group:
[0009] R-OH+OCN-R'-NCO→RO-CO-NH-R'-NCO;
[0010] The resulting urethane bonds are highly stable and are the basis of the polyurethane network. The diphenylmethane diisocyanate molecule contains two isocyanate groups that can react with two different hydroxyl molecules. This bifunctionality gives the resulting prepolymer a linear structure on the main chain and provides more possibilities for subsequent reactions. Polyethylene adipate glycol provides a flexible chain segment, and its linear structure gives the prepolymer good mechanical properties and elasticity. The introduction of fluorinated polyether further improves the chemical resistance and environmental stability of the material through its hydrophobicity and low surface energy.
[0011] Based on the synergistic effect of dynamic chemical bonds and physical interactions in polyurethane elastomers, the acylhydrazone bond (C=NNH-) is a dynamic covalent bond that can break and reform under external stimuli (such as heat, humidity or pH changes). When the polyurethane network breaks under external forces, the acylhydrazone bond can recombine through a dynamic bond exchange process to repair the cracks. Disulfides provide reversible disulfide bonds (-SS-), which undergo dynamic exchange reactions under heat or light stimulation:
[0012]
[0013] After the disulfide bond at the crack breaks, the molecular chain forms new chemical bonds through dynamic rearrangement to close the crack. The disulfide bond enhances the dynamic performance of self-healing, which is significant under high temperature conditions on summer roads.
[0014] At the same time, silane-modified EPDM particles are added, and the ethoxy group (-OEt) of γ-mercaptopropyl triethoxysilane directly reacts with the active points on the surface of the EPDM particles (such as unsaturated double bonds or surface oxidation products) to form stable chemical bonds, and the mercapto group (-SH) remains on the surface of the modified EPDM, providing active sites for further reaction with the polyurethane matrix. In the subsequent dispersion and curing process, the mercapto group reacts with the isocyanate group (-NCO) in the polyurethane matrix to form a thiocarbamate bond (-NH-CS-), which enhances the chemical bonding between the EPDM and the matrix:
[0015] R-NCO+R'-SH→R-NH-CS-R';
[0016] The surface of the modified EPDM rubber particles changes from non-polar to partially polar, which enhances its dispersibility and interfacial compatibility in the polar polyurethane matrix.
[0017] In addition, the present invention adds dibutyltin dilaurate, triphenylphosphine and organosilicon synergist. Dibutyltin dilaurate is a highly efficient organotin catalyst that mainly accelerates the nucleophilic addition reaction between isocyanate (-NCO) and hydroxyl (-OH) or amino (-NH2). The catalytic process enhances the electrophilicity of carbon atoms and accelerates the reaction with nucleophilic reagents (-OH or -NH2) through isocyanate in the complex reaction. In the chain extension stage, dibutyltin dilaurate ensures that the amino group (PACM) reacts quickly with the -NCO group in the prepolymer to generate long-chain polyurethane.
[0018] Triphenyl phosphine decomposes at high temperatures to generate phosphoric acid compounds, which promote carbonization on the surface of the polyurethane matrix and isolate oxygen and heat. During the combustion process, the released phosphorus-based compounds can capture free radicals generated by combustion, inhibit free radical chain reactions, and reduce the heat release rate. Triphenyl phosphine improves the structural integrity of the material under high temperature or thermal stimulation conditions, protects dynamic bonds and molecular segments, extends the service life of self-healing elastomer materials, provides a thermally stable environment, and avoids excessive decomposition of dynamic cross-linked networks (such as disulfide bonds).
[0019] Silicone enhancer is a surfactant material with a hydrophobic siloxane skeleton and a hydrophilic polyether segment. The siloxane segment forms a low surface energy film on the surface of the elastomer, improving the surface lubricity and pollution resistance of the material and preventing the polyurethane elastomer from being contaminated by environmental factors during the early curing process.
[0020] Furthermore, the fluorinated polyether polyol used in the self-healing polyurethane elastomer material is a fluorinated polyether polyol with a molecular weight of 3000 g / mol, which includes the following raw materials in parts by weight: 65 to 75 parts of perfluoropropylene oxide, 5 to 10 parts of tetrafluoroethylene-hexafluoropropylene copolymer, 10 to 20 parts of propylene carbonate, 3 to 7 parts of terminal hydroxyl polyethylene glycol, 0.01 to 0.05 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum, and 0.01 to 0.03 parts of 2,6-di-tert-butyl-p-cresol.
[0021] Furthermore, the dynamic reversible bond monomer containing acylhydrazone bond functionalized small molecules used in the self-healing polyurethane elastomer material includes the following raw materials by weight: 10 to 20 parts of terephthaloyl hydrazide, 15 to 25 parts of isophthalaldehyde, 25 to 35 parts of polyethylene glycol, 15 to 25 parts of 1,4-butanediol, 1 to 3 parts of graphene oxide, 0.3 to 0.7 parts of glacial acetic acid catalyst and 10 to 15 parts of anhydrous ethanol.
[0022] Furthermore, the disulfide used in the self-healing polyurethane elastomer material includes the following raw materials by weight: 30-45 parts of dibenzoyl disulfide, 25-35 parts of diethyl disulfide, 15-25 parts of 3,3'-thiodipropionic acid and 8-13 parts of diphenylacetyl disulfide.
[0023] Furthermore, the silane-modified EPDM rubber particles used in the self-healing polyurethane elastomer material include the following raw materials by weight: 85-90 parts of EPDM rubber particles, 3-5 parts of γ-mercaptopropyltriethoxysilane and 10-12 parts of γ-aminopropyltriethoxysilane.
[0024] Furthermore, the silane-modified EPDM rubber particles used in the self-healing polyurethane elastomer material are prepared by the following steps: the EPDM rubber particles are washed and dried at 100-120°C for 2-3 hours, γ-mercaptopropyltriethoxysilane and γ-aminopropyltriethoxysilane are mixed and stirred in proportion for 2-3 minutes, the EPDM rubber particles are added to the mixed solution at 80-100°C, stirred for reaction for 2-3 hours, and dried at 80-100°C for 3-5 hours after the reaction.
[0025] Furthermore, the nano-filling material used in the self-healing polyurethane elastomer material includes the following raw materials by weight: 45-55 parts of graphene oxide and 55-45 parts of multi-walled carbon nanotubes.
[0026] The present invention adds graphene oxide to the dynamic reversible bond monomer containing acylhydrazone bond functionalized small molecules and nano filling materials. The surface of the added graphene oxide is rich in polar functional groups such as hydroxyl (-OH) and carboxyl (-COOH), and can interact with the segments in the polyurethane matrix by forming chemical bonds. The carboxyl groups on the surface of the graphene oxide react with the isocyanate groups through the hydroxyl (-OH) in the carboxylic acid group to generate carbamate bonds (-NH-COO-), the carboxyl groups of the graphene oxide react with the hydroxyl groups in the polyurethane segments to generate ester bonds (-CO-O-), the hydroxyl groups on the surface of the graphene oxide directly react with the isocyanate groups in the matrix to form carbamate bonds, the formation of chemical bonds is irreversible, the interface bonding force between the graphene oxide and the matrix is significantly improved, and the mechanical properties of the material as a whole are enhanced.
[0027] Multi-walled carbon nanotubes are added to the nanofiller material. The multi-walled carbon nanotubes have a high aspect ratio and high mechanical strength, and serve as rigid fillers to enhance the strength of the polyurethane elastomer. During the high-speed dispersion process, strong shear forces disperse the EPDM particles modified with γ-mercaptopropyltriethoxysilane, graphene oxide and multi-walled carbon nanotubes evenly in the matrix, avoiding agglomeration of the fillers.
[0028] Furthermore, the stabilizer material used in the self-healing polyurethane elastomer material includes one or more of UV absorbers UV326, UV531 or UV328, light stabilizer 944 and antioxidant 1010. Preferably, it includes 10-15 parts of UV absorber UV326, 15-25 parts of UV531, 15-18 parts of UV328, 30-35 parts of light stabilizer 944, and 20-25 parts of antioxidant 1010.
[0029] The method for preparing the self-healing polyurethane elastomer material of the present invention comprises the following steps:
[0030] (1) heating the fluorine-containing polyether polyol and polyethylene adipate glycol diol to 70-80° C., stirring and mixing under nitrogen protection, adding diphenylmethane diisocyanate, controlling the NCO content to 7.0%-8.5%, and reacting at 80-90° C. for 2-3 hours to obtain a prepolymer;
[0031] (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule and a disulfide to the prepolymer, and continuing the reaction at 70 to 80° C. for 1 to 2 hours;
[0032] (3) adding silane-modified EPDM rubber particles and nanofiller materials, stirring and dispersing them uniformly, and cooling the mixture to 60-70° C.;
[0033] (4) adding 4,4'-diaminodicyclohexylmethane chain extender, dibutyltin dilaurate, triphenylphosphine, stabilizer and organosilicon enhancer, and stirring well to form a self-healing polyurethane elastomer material.
[0034] When preparing the prepolymer, the reaction temperature is controlled at 80-90° C., which not only promotes the reaction speed but also avoids side reactions. The operation is carried out under nitrogen protection to prevent moisture or oxygen from reacting with -NCO groups, thereby ensuring high purity and high reactivity of the prepolymer.
[0035] The seamless telescopic structure of the present invention comprises a carbon fiber steel composite plate arranged in an expansion joint slot, external angle steels arranged on both sides of the expansion joint slot, a self-healing polyurethane interface adhesive layer coated on the inner side of the external angle steel, an internal angle steel arranged on the inner side of the external angle steel and formed as a whole with the external angle steel, an elastic stabilizing element composed of springs and steel rods laid layer by layer horizontally, and a self-healing polyurethane elastomer material layer filled in the expansion joint slot and formed of the above-mentioned self-healing polyurethane elastomer material.
[0036] Furthermore, the raw materials used in the self-healing polyurethane interface adhesive layer of the present invention include, by weight: 35-45 parts of isophorone diisocyanate, 25-35 parts of polycaprolactone diol, 5-10 parts of 4,4'-diaminodicyclohexylmethane chain extender, 3-7 parts of dynamic reversible bond monomers containing acylhydrazone bond functionalized small molecules, 1-3 parts of multi-walled carbon nanotubes, 2-4 parts of γ-aminopropyltriethoxysilane, 0.1-0.3 parts of dibutyltin dilaurate, 0.2-0.4 parts of silicone synergist and 0.1-0.2 parts of light stabilizer.
[0037] The self-healing polyurethane interface adhesive material of the present invention is based on polyvinyl lactone diol and isophorone diisocyanate. The hydroxyl group (-OH) in PCL reacts with the isocyanate group (-NCO) of IPDI to generate a polyurethane segment. The reaction formula is as follows:
[0038] R-OH+R'-NCO→RO-CO-NH-R';
[0039] Based on the prepared prepolymer, a functionalized small molecule containing an acylhydrazone bond is added. The acylhydrazone bond (C=N-NH-C) has a dynamically reversible chemical property and can achieve structural repair through bond breaking and recombination during the self-healing process. The acylhydrazone bond in the functionalized small molecule undergoes a secondary reaction with the NCO group in the prepolymer, further introducing a dynamic bond to give the material self-healing properties.
[0040] The acylhydrazone bond (C=N-NH-C) is a dynamically reversible chemical bond that can break and reform under certain conditions (such as temperature increase or chemical environment changes). When the polyurethane adhesive is damaged by external forces or cracks are formed, the acylhydrazone bond will break and release new reaction sites. When the crack surface is re-contacted and the environment is suitable (such as 70-80°C), the acylhydrazone bond will reform through a chemical equilibrium mechanism to restore the integrity of the material.
[0041] Acylhydrazone bond reaction formula:
[0042] In the damaged area, after the acylhydrazone bond breaks, the free ends of the molecular chains re-form chemical bonds, thereby restoring the integrity of the material. After the dynamic bond breaks, the polyurethane molecular chain has a high molecular segment mobility at a certain temperature. The molecular chain migrates to the crack area and recombine through chemical reactions to achieve crack repair.
[0043] At the same time, multi-walled carbon nanotubes and γ-aminopropyltriethoxysilane are added, and the amino groups in γ-aminopropyltriethoxysilane can react with the surface of carbon nanotubes through chemical bonds, thereby improving its dispersibility and compatibility in organic systems. The reacted multi-walled carbon nanotubes are added to the polyurethane prepolymer and evenly dispersed, thereby enhancing the mechanical properties, electrical conductivity and thermal stability of the material through the multi-walled carbon nanotubes, and providing stronger interface properties for the adhesive. The bonding strength of the multi-walled carbon nanotube-enhanced polyurethane adhesive comes from the comprehensive results of the chemical bonding, physical intercalation and carbon nanotube reinforcement between the polyurethane and the steel base surface. The NCO group in the polyurethane prepolymer can react with the hydroxyl group on the steel surface or the adsorbed moisture to generate a urea group (-NH-CO-NH-).
[0044] The amino groups (from γ-aminopropyltriethoxysilane) or hydroxyl groups introduced on the surface of functionalized multi-walled carbon nanotubes can react with NCO groups to further form chemical bonds, thereby enhancing the bonding strength and interface bonding performance. This mainly includes the following three aspects:
[0045] (1) Functionalized multi-walled carbon nanotubes are evenly dispersed to achieve toughening effects through their high strength, high modulus and high specific surface area. Multi-walled carbon nanotubes have excellent mechanical properties and can effectively bear and disperse stress under the action of external forces. At the same time, they transfer stress to the matrix through interfacial action, thereby improving the tensile strength and fracture toughness of the material. Its high specific surface area enhances the interfacial bonding with the matrix, so that cracks are guided by carbon nanotubes to deflect and bridge during propagation, extending the crack path and consuming more energy, thereby significantly improving the crack resistance of the binder. In addition, the nanoscale network structure formed by carbon nanotubes in the matrix further enhances the overall toughness of the material, and absorbs the energy of the applied load through micro-bending and sliding behavior, ultimately significantly improving the mechanical properties and durability of the binder. A strong toughening effect is formed in the binder system.
[0046] (2) The high specific surface area of MWCNTs increases the contact area with the steel surface, which helps to form more chemical bonds or physical intercalation.
[0047] (3) Functionalized multi-walled carbon nanotubes act as molecular bridges between the adhesive and steel interface, dispersing stress through their excellent mechanical properties and preventing adhesion failure caused by interfacial stress concentration. Carbon nanotubes have good thermal and electrical conductivity, which can evenly disperse heat or charge, reduce interfacial thermal stress caused by differences in thermal expansion coefficients, and improve adhesion stability.
[0048] In addition, the added chain extender 4,4'-diaminodicyclohexylmethane plays an important role in the preparation of polyurethane binders. 4,4'-diaminodicyclohexylmethane is a chain extender containing two active amino (-NH2) groups, which can chemically react with the unreacted isocyanate (-NCO) groups in the prepolymer to form longer and more cross-linked polyurethane molecular chains.
[0049] In the polyurethane prepolymer, due to the control of the reaction ratio, some isocyanate (-NCO) groups do not react completely with the hydroxyl (-OH) groups and remain at the end groups of the molecular chain. After adding 4,4'-diaminodicyclohexylmethane, its amino group (-NH2) reacts with these residual NCO groups to form urea groups (-NH-CO-NH-). The reaction formula is as follows:
[0050] R-NCO+H2N-R'-NH2→R-NH-CO-NH-R'-NH-CO-NH-R
[0051] This reaction significantly increases the molecular weight and chain flexibility of the polyurethane binder by connecting multiple prepolymer molecular chains.
[0052] The introduction of chain extenders effectively extends the length of the polyurethane molecular chain, allowing the polyurethane binder molecular chain to form a flexible but high-strength cross-linked network after curing. Longer molecular chains can provide greater intermolecular forces and improve the mechanical properties of the material. The urea group (-NH-CO-NH-) generated by chain extension of 4,4'-diaminodicyclohexylmethane can form hydrogen bonds at the interface between the binder and the substrate, interacting with the polar groups on the surface of the steel, thereby significantly enhancing the interfacial bonding strength between the binder and the substrate.
[0053] The addition of 4,4'-diaminodicyclohexylmethane makes the molecular chains in the system have better flexibility and dynamic adjustment ability. When the substrate is subjected to external force, the molecular chains can rearrange and adjust, thereby maintaining the bonding strength and toughness. The urea group generated by 4,4'-diaminodicyclohexylmethane has higher thermal stability than ordinary carbamate (-NH-CO-O-), which can enhance the mechanical properties of polyurethane materials in high temperature environments; the extended molecular chain and cross-linked network structure of 4,4'-diaminodicyclohexylmethane reduce the free mobility of polyurethane molecules, thereby slowing down the material aging process caused by the external environment (such as oxidation, ultraviolet rays or moisture).
[0054] In addition, the present invention also adds dibutyltin dilaurate, organosilicon synergist, and light stabilizer. Dibutyltin dilaurate activates the isocyanate group through its tin center, making it easier to undergo nucleophilic addition reaction with hydroxyl group, thereby generating carbamate (-NH-CO-O-). The tin atom of DBTDL coordinates with the NCO group, reduces the activation energy of the reaction, accelerates the reaction rate, and the generated intermediate helps to improve the selectivity of the reaction and reduce side reactions (such as NCO group self-polymerization). In the chain extension stage, DBTDL can also catalyze the reaction of NCO group and amine group to generate urea group (-NH-CO-NH-). This process is crucial for forming a strong and tough molecular chain structure. The catalytic effect of dibutyltin dilaurate ensures that the reaction rate of NCO group and various active hydrogen groups in the system is balanced, thereby avoiding the problem of uneven crosslinking or gelation caused by too fast reaction, and improving the uniformity of the final binder. The organosilicon synergist partially reduces the surface tension of the system, makes it easier for the polyurethane binder to spread to the surface of the substrate, enhances its interface bonding with the substrate, and helps to improve the adhesion performance of the binder. The introduction of flexible segments in the polyether part can buffer the internal stress of the material and improve the toughness and crack resistance of the binder. The low modulus characteristics of the siloxane part further improve the elasticity of the material, enabling it to adapt to the deformation of the substrate under stress conditions. Silicone enhancers can also help to evenly disperse nanomaterials such as carbon nanotubes to avoid agglomeration and improve the reinforcement effect. Light stabilizers extend the service life of materials by capturing free radicals and inhibiting oxidation chain reactions. Polyurethane materials are easily affected by heat, light and oxygen during processing and use, causing macromolecular chains to break and generate free radicals.
[0055] In addition to the above, the seamless telescopic structure of the present invention combines a self-healing polyurethane elastomer material with a self-healing polyurethane interface adhesive, and the two are wet-bonded during use. The elastomer contains polyethylene adipate glycol diol and fluorine-containing polyether polyol. The hydroxyl groups on these molecules react with the isocyanate in the adhesive to form a polyurethane bond (R-NH-COOR'). The isocyanate in the adhesive can also react with 4,4'-diaminodicyclohexylmethane or other amino-active substances to form a urea bond (R-NH-C(O)-NH-R'). The γ-aminopropyltriethoxysilane in the adhesive and the γ-mercaptopropyltriethoxysilane in the elastomer undergo a silanization reaction at the interface, condensing with the surface hydroxyl groups (OH) of the inorganic substrate (such as angle steel) to form a silicon-oxygen bond (Si-O-Si), providing a chemical bond. The silicon-oxygen bond has a high degree of chemical stability and moisture resistance, providing a long-lasting bonding ability for the interface. Acylhydrazone bond (C=N-NH): Both the adhesive and the elastomer contain acylhydrazone functionalized monomers. This dynamic bond can break and recombine under wet bonding conditions to achieve a self-healing function. The disulfide bond of the disulfide in the elastomer breaks at the interface and combines with the sulfur group of the adhesive to further form a dynamic bridge.
[0056] The multi-walled carbon nanotubes in the binder form a physical network by distributing in the interface area, uniformly dispersing the interface stress and preventing the extension of microcracks. The surface groups of carbon nanotubes (such as hydroxyl and carboxyl) interact with the active groups in the binder and elastomer (such as -NCO, -OH) in a secondary manner (such as hydrogen bonding and van der Waals force), further strengthening the interface. The surface active groups (epoxy and carboxyl) of graphene oxide can react with isocyanate or form hydrogen bonds, which can enhance the chemical bonding while improving the mechanical strength and thermal stability of the interface. γ-mercaptopropyl triethoxysilane modified EPDM reacts with the isocyanate in the binder through the surface mercapto group (-SH) to form a stable urea bond. At the same time, the micro-rough structure of the particles provides mechanical bite force. The mechanical bite action and chemical bonding work together to improve the shear strength and tensile properties of the interface. Fluorinated polyethers and silicone enhancers reduce the surface tension of the binder, enhance the wettability of the binder on the elastomer surface, and improve the contact efficiency of the chemical reaction.
[0057] When interfacial cracks form, acylhydrazone bonds and disulfide bonds are preferentially broken to absorb stress. After the cracks disappear, these dynamic bonds are reorganized through chemical equilibrium to restore the integrity of the interface. After the crack occurs, the moisture in the environment promotes the dynamic reaction of the acylhydrazone bonds, and the crack repair speed is accelerated. When the temperature rises in summer, the breaking and recombination process of disulfide bonds is accelerated, which improves the self-healing efficiency. Carbon nanotubes and graphene oxide concentrate stress at the crack tip, inducing a faster recombination of dynamic chemical bonds, while filling the crack area to enhance the mechanical properties after repair.
[0058] Furthermore, the raw materials used in the self-healing polyurethane interface adhesive layer of the seamless telescopic structure of the present invention are prepared by the following steps:
[0059] (1) heating polycaprolactone diol to 70-80° C., stirring and melting under nitrogen protection, adding isophorone diisocyanate, controlling the NCO content to 4.0%-5.0%, and reacting at 80-90° C. for 2-3 hours to obtain a polyurethane prepolymer;
[0060] (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule to the prepolymer, and continuing the reaction at 70-80° C. for 1-2 hours;
[0061] (3) mixing carbon nanotubes and γ-aminopropyltriethoxysilane, and adding the mixture to the system of step (2) to uniformly disperse the mixture;
[0062] (4) adding 4,4'-diaminodicyclohexylmethane, dibutyltin dilaurate, an organosilicon enhancer and a light stabilizer, and stirring evenly at 60-70° C. to obtain a self-healing polyurethane interface adhesive material.
[0063] The present invention heats polycaprolactone diol to 70-80° C., stirs and melts it under nitrogen protection to make it reach a uniform liquid state, thereby avoiding decomposition or oxidation of the polycaprolactone diol, and providing a uniform reaction environment for subsequent reactions. Isophorone diisocyanate is slowly added to the molten polycaprolactone diol system to control the NCO content to 4.0%-5.0%. This step needs to ensure that the two raw materials are fully mixed, and the side reaction caused by excessive local concentration is reduced by gradual addition. At 80-90° C., the hydroxyl group (-OH) in the polycaprolactone diol and the isocyanate group (-NCO) of IPDI undergo addition reaction to generate polyurethane segments and release heat. This reaction avoids excessive crosslinking by controlling temperature and time (2-3 hours), ensuring that the final prepolymer has the expected molecular weight and active end groups.
[0064] Furthermore, the carbon fiber steel composite plate of the seamless expansion device of the present invention comprises a steel base layer, an epoxy resin interface bonding layer located on the steel base layer, and a carbon fiber reinforcement layer located on the epoxy resin interface bonding layer;
[0065] The raw materials used in the epoxy resin interface bonding layer include the following raw materials by weight: 100 parts of bisphenol A epoxy resin, 10-15 parts of active diluent AGE, 50-60 parts of meta-xylylenediamine, 10-20 parts of carboxyl-terminated liquid nitrile rubber, and 3-5 parts of nano silicon dioxide;
[0066] The carbon fiber reinforcement layer is 3 to 5 layers of carbon fiber fabrics arranged alternately at 0° and 90° directions.
[0067] Furthermore, the carbon fiber steel composite plate of the seamless telescopic device of the present invention is also provided with a rubber layer to isolate the carbon fiber steel composite plate from direct contact with the self-healing polyurethane elastomer material layer.
[0068] Beneficial effects: Compared with the prior art, the significant advantages of the present invention are: the self-healing polyurethane elastomer material based on dynamic reversible covalent bonds not only has excellent durability, but also can effectively repair cracks and damage through a self-healing mechanism, greatly extending the service life of the device; and the present invention enhances the mechanical strength and sealing of the splicing parts through an innovative splicing structure design, avoiding the stress concentration and sealing failure problems that are prone to occur in traditional splicing methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 It is a schematic diagram of the seamless telescopic structure of the present invention. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings.
[0071] It should be noted that the specific substances included in the fluorinated polyether polyol, the acylhydrazone bond-containing functionalized small molecule, the disulfide, the nanofiller material and the stabilizer used in the present invention can be directly blended and compounded during preparation.
[0072] In addition, the raw materials used in the present invention can be purchased from the market. The CAS numbers or manufacturers of some raw materials are shown in Table 1 below.
[0073] Table 1 CAS number or manufacturer of raw materials used in the present invention
[0074]
[0075]
[0076]
[0077] Example 1
[0078] (1) Self-healing polyurethane elastomer materials
[0079] This embodiment 1 is a self-healing polyurethane elastomer material based on dynamic reversible covalent bonds, and its raw material components are shown in Table 2 below.
[0080] Table 2 Component contents of self-healing polyurethane elastomer materials in Example 1
[0081] Serial number raw material Content / portion 1 Methylene diphenyl diisocyanate (MDI) 31 2 Fluorinated polyether polyols 21.515 3 Polyethylene adipate glycol 12 4 4,4'-Diaminodicyclohexylmethane 8 5 Acylhydrazone-functionalized small molecules 5.775 6 Disulfide 3 7 Silane-modified EPDM rubber particles 15 8 Nano filling materials 2 9 Triphenylphosphine 1.5 10 Dibutyltin dilaurate 0.2 11 Stabilizer 0.15 12 Silicone synergist 0.3
[0082] Among them, the component contents of fluorinated polyether polyols are shown in Table 2. The component contents of small molecules functionalized with acylhydrazone bonds are shown in Table 3. The component contents of disulfides are shown in Table 4. The component contents of silane-modified EPDM rubber particles are shown in Table 5. The component contents of nanofillers are shown in Table 6. The component contents of stabilizers are shown in Table 7.
[0083] Table 3 Component contents of fluorinated polyether polyols
[0084] Serial number raw material Content / portion 1 Perfluoropropylene oxide 70 2 Tetrafluoroethylene-hexafluoropropylene copolymer 8 3 Propylene carbonate 15 4 Hydroxyl-terminated polyethylene glycol 5 5 1,3-Divinyl-1,1,3,3-tetramethyldisiloxane platinum 0.03 6 2,6-Di-tert-butyl-p-cresol 0.02
[0085] Table 4 Component contents of small molecules functionalized with acylhydrazone bonds
[0086] Serial number raw material Content / portion 1 Terephthaloyl hydrazide 15 2 Isophthalaldehyde 20 3 Polyethylene glycol 30 4 1,4-Butanediol 20 5 Graphene oxide 2 6 Glacial acetic acid catalyst 0.5 7 Anhydrous ethanol 12
[0087] Table 5 Component content of disulfide
[0088] Serial number raw material Content / portion 1 Benzoyl disulfide 40 2 Diethyl disulfide 30 3 3,3'-Thiodipropionic acid 20 4 Diphenylacetyl disulfide 10
[0089] Table 6 Component content of silane-modified EPDM rubber particles
[0090] Serial number raw material Content / portion 1 EPDM rubber granules 88 2 γ-Mercaptopropyltriethoxysilane 4 3 γ-Aminopropyltriethoxysilane 11
[0091] Table 7 Component content of nanofiller materials
[0092] Serial number raw material Content / portion 1 Graphene oxide 50 2 Multi-walled carbon nanotubes 50
[0093] Table 8 The component contents of the stabilizer are as follows
[0094] Serial number raw material content 1 Ultraviolet absorber UV326 46 2 Light Stabilizer 944 32 3 Antioxidant 1010 22
[0095] The self-healing polyurethane elastomer material of Example 1 is prepared by the following steps:
[0096] (1) heating the fluorine-containing polyether polyol and polyethylene adipate diol to 75° C., stirring and mixing under nitrogen protection, adding diphenylmethane diisocyanate, controlling the NCO content to 8.0%, and reacting at 80° C. for 2 h to obtain a prepolymer;
[0097] (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule and a disulfide to the prepolymer and continuing the reaction at 75°C for 2 hours;
[0098] (3) adding silane-modified EPDM rubber particles and nanofiller, stirring and dispersing them uniformly, and cooling to 60° C.; wherein the silane-modified EPDM rubber particles are prepared by the following steps: washing the EPDM rubber particles and drying them at 120° C. for 3 h, mixing γ-mercaptopropyl triethoxysilane and γ-aminopropyl triethoxysilane in proportion and stirring for 3 min, adding the EPDM rubber particles to the mixed solution at 100° C. and stirring for 3 h, and drying at 8100° C. for 5 h after the reaction;
[0099] (4) adding 4,4'-diaminodicyclohexylmethane chain extender, dibutyltin dilaurate, triphenylphosphine, stabilizer and organosilicon enhancer, and stirring well to form a self-healing polyurethane elastomer material.
[0100] The self-healing polyurethane elastomer material prepared in Example 1 was tested for performance, and the results obtained are shown in Table 9 below.
[0101] Table 9 Performance indexes of self-healing polyurethane elastomer materials of Example 1
[0102]
[0103] It can be seen from Table 9 that the self-healing polyurethane elastomer material based on dynamic reversible covalent bonds in Example 1 exhibits excellent mechanical properties, self-healing ability and environmental durability. The material exhibits excellent results in multiple performance tests, such as high strength, high elongation at break and rapid recovery of self-healing performance. At the same time, it is completely sealed and impermeable, and there is no obvious performance degradation under harsh environmental conditions.
[0104] (2) Self-healing polyurethane interface adhesive
[0105] The raw material components of the self-healing polyurethane interface adhesive of Example 1 are shown in Table 10. The content of the component containing the acylhydrazone bond functionalized small molecule is shown in Table 4.
[0106] Table 10 Component contents of self-healing polyurethane interface adhesive in Example 1
[0107]
[0108]
[0109] The self-healing polyurethane interface adhesive of Example 1 is prepared by the following steps:
[0110] (1) heating polycaprolactone diol to 80° C., stirring and melting under nitrogen protection, adding isophorone diisocyanate, controlling the NCO content to 4.5%, and reacting at 80-90° C. for 2 hours to obtain a polyurethane prepolymer;
[0111] (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule to the prepolymer and continuing the reaction at 80°C for 2 h;
[0112] (3) mixing carbon nanotubes and γ-aminopropyltriethoxysilane, and adding the mixture to the system of step (2) to uniformly disperse the mixture;
[0113] (4) adding 4,4'-diaminodicyclohexylmethane, dibutyltin dilaurate, an organosilicon enhancer and a light stabilizer, and stirring evenly at 70° C. to obtain a self-healing polyurethane interface adhesive material.
[0114] The self-healing polyurethane interface adhesive prepared in Example 1 was tested for performance, and the results obtained are shown in Table 11 below.
[0115] Table 11 Performance indicators of self-healing polyurethane interface adhesive of Example 1
[0116] Test items Test Standards Test Results Steel bond strength ASTMD1002 19MPa Interfacial peel strength ASTMD1876 38N / mm Tensile strength(MPa) GB / T528-2009 17.5 Elongation at break (%) GB / T528-2009 664 Modulus (100% stretch) GB / T528-2009 5 Healing efficiency (shear strength) After breaking, place at 70℃ for 24 hours >85% recovery Healing efficiency (elongation) After breaking, place at 70℃ for 24 hours >90% recovery Operation time (minutes) 25℃, 50% humidity 25 Curing time (hours) Under the condition of 60℃ 2.5
[0117] The self-healing polyurethane interface adhesive of Example 1 exhibits excellent adhesion and mechanical properties, especially in terms of steel bonding and interface bonding strength, reaching 19MPa and 38N / mm respectively, meeting the high performance requirements of engineering applications. At the same time, the adhesive exhibits excellent self-healing ability after fracture, and its healing efficiency of shear strength and elongation exceeds 85% and 90% respectively. In addition, the 25-minute operation time and 2.5-hour fast curing time make it convenient and efficient in practical applications. These performance indicators show that the material has broad application prospects in the fields of expansion joint angle steel sealing, interface repair and high-performance bonding.
[0118] (3) Seamless telescopic structure
[0119] The seamless telescopic structure of the embodiment 1 has a structure as follows: Figure 1 As shown, it includes a carbon fiber steel composite plate 2 arranged in the expansion joint slot 1, an outer angle steel 3 attached to both sides of the expansion joint slot 1, a self-healing polyurethane interface adhesive layer 4 coated on the inner side of the outer angle steel 3, an inner angle steel 4 arranged on the inner side of the outer angle steel 3 and forming an integral body with the outer angle steel 3, an elastic stabilizing element 5 (which can be a combination of a spring and a steel rod) laid layer by layer horizontally, and a self-healing polyurethane elastomer material layer 6 filled in the expansion joint slot 1.
[0120] The construction method of the seamless telescopic structure comprises the following steps:
[0121] (1) Use a dust-free cutting machine to evenly cut on both sides of the expansion joint to form a notch (e.g., 80 cm wide) and clean the notch to remove the slurry on the surface of the concrete cushion layer.
[0122] (2) Carbon fiber steel composite plates (for example, 15 mm thick and 40 cm wide) are laid out on both sides of the expansion joint with equal width, and fixed to the concrete beam with limit pins. After the carbon fiber steel composite plates are laid out, rubber sheets are laid on the steel plates to isolate the composite plates from direct contact with the elastomer;
[0123] (3) Install the outer angle steel. The highest point of the outer facade of the outer angle steel should be flush with the original asphalt pavement. The outer angle steel should be welded to the original expansion joint door-shaped steel bar with welding rods.
[0124] (4) Pour fast-setting C50 steel fiber concrete in the anchoring area and sprinkle water to cure for 12 hours after pouring.
[0125] (5) Apply self-healing polyurethane interface adhesive to the inner interface of the outer angle steel. The coating amount can be 0.6kg / m 2 .
[0126] (6) Pour the first layer of self-healing polyurethane elastomer with a thickness of 2 cm.
[0127] (7) Install the inner angle steel and fix it to the outer angle steel with bolts to form an integral whole. Pour the self-healing polyurethane concrete again with a thickness of 4.5 cm. Simultaneously install the elastic stabilizing elements at intervals of 15 cm and fix them in the holes of the inner angle steel with clips. Wait for initial curing for 1 hour.
[0128] (8) Pour the last layer of self-healing polyurethane elastomer with a thickness of about 0.5 cm, flush with the original asphalt pavement and anchoring concrete. Use a scraper to level it and allow it to cure. Traffic can be opened after 24 hours of curing.
[0129] The carbon fiber steel composite plate arranged above the bridge structure seam in the seamless telescopic structure is composed of a steel matrix layer and a carbon fiber reinforcement layer through an epoxy resin interface bonding layer. The steel matrix layer is 13 to 15 mm, the steel matrix is Q355B, the sandblasting rust removal grade is not less than Sa2.5, and the roughness is 80 μm; the epoxy resin interface bonding layer includes 100 parts of bisphenol A epoxy resin E44, 12 parts of active diluent AGE, 55 parts of meta-phenylenediamine (m-PDA), 13 parts of terminal carboxyl liquid nitrile rubber (CTBN), and 4 parts of 7 to 15 nanometer silica thickener; the carbon fiber reinforcement layer is 3 to 5 layers of carbon fiber fabrics arranged alternately in the 0° and 90° directions, vacuum hot pressed at 180°C and 2MPa for curing for 2 hours, and the thickness is 5 mm.
[0130] The performance results of the carbon fiber steel composite plate are shown in Table 12 below.
[0131] Table 12 Performance results of carbon fiber steel composite plate
[0132] Test items Test Standards Test Results Tensile strength(MPa) GB / T6396-2008 1175 Bending strength(MPa) GB / T6396-2008 778 Shear strength(MPa) GB / T6396-2008 68.4 <![CDATA[Impact strength (kJ / m 2 )]]> GB / T6396-2008 52 Interface bonding strength (MPa) GB / T6396-2008 33 Fatigue life (high frequency alternating load) <![CDATA[±100MPa、50Hz、10 6 Cycle]]> No cracks or peeling Fatigue life (high and low temperature alternating environment) -20℃ to 60℃, 50 cycles No noticeable performance degradation
[0133] In addition, the seamless telescopic structure prepared by the present invention was subjected to performance testing, as follows:
[0134] The salt spray test (ASTM B117) showed that the device had no cracks or performance degradation after 1000 hours; the fatigue test (high frequency alternating load ±100MPa, 50Hz, 10 6 The device has no cracks or peeling after 2 cycles (cycles); in addition, as a seamless expansion joint crack repair material, the material's fatigue resistance after crack filling is restored to more than 95% of the initial level, and the operation time is 25 minutes, and the construction is simple; in addition, the overall structure of the device has 0 water seepage under the conditions of water seepage test, and the self-healing polyurethane elastomer has 0 voids, which has a good sealing effect. The overall verification shows that the present invention significantly improves the reliability and economy of engineering structures and has a wide range of promotion value.
[0135] Example 2
[0136] (1) Self-healing polyurethane elastomer materials
[0137] This embodiment 2 is a self-healing polyurethane elastomer material based on dynamic reversible covalent bonds, and its raw material components are shown in Table 13 below.
[0138] Table 13 Component contents of self-healing polyurethane elastomer materials in Example 2
[0139]
[0140]
[0141] Among them, the component contents of fluorinated polyether polyols are shown in Table 14. The component contents of small molecules functionalized with acylhydrazone bonds are shown in Table 15. The component contents of disulfides are shown in Table 16. The component contents of silane-modified EPDM rubber particles are shown in Table 17. The component contents of nanofillers are shown in Table 18. The component contents of stabilizers are shown in Table 19.
[0142] Table 14 Component contents of fluorinated polyether polyols
[0143] Serial number raw material Content / portion 1 Perfluoropropylene oxide 68 2 Tetrafluoroethylene-hexafluoropropylene copolymer 6 3 Propylene carbonate 12 4 Hydroxyl-terminated polyethylene glycol 6 5 1,3-Divinyl-1,1,3,3-tetramethyldisiloxane platinum 0.04 6 2,6-Di-tert-butyl-p-cresol 0.01
[0144] Table 15 Component contents of small molecules functionalized with acylhydrazone bonds
[0145]
[0146]
[0147] Table 16 Component content of disulfide
[0148] Serial number raw material Content / portion 1 Benzoyl disulfide 38 2 Diethyl disulfide 28 3 3,3'-Thiodipropionic acid 22 4 Diphenylacetyl disulfide 11
[0149] Table 17 Component content of silane-modified EPDM rubber particles
[0150] Serial number raw material Content / portion 1 EPDM rubber granules 86 2 γ-Mercaptopropyltriethoxysilane 3 3 γ-Aminopropyltriethoxysilane 12
[0151] Table 18 Component content of nanofiller materials
[0152] Serial number raw material Content / portion 1 Graphene oxide 45 2 Multi-walled carbon nanotubes 55
[0153] Table 19 The component contents of the stabilizer are as follows
[0154] Serial number raw material content 1 Ultraviolet absorber UV326 12 2 Ultraviolet absorber UV531 20 3 Ultraviolet absorber UV328 16 4 Light Stabilizer 944 34 5 Antioxidant 1010 23
[0155] The self-healing polyurethane elastomer material of Example 2 is prepared by the following steps:
[0156] (1) heating the fluorine-containing polyether polyol and polyethylene adipate diol to 80° C., stirring and mixing under nitrogen protection, adding diphenylmethane diisocyanate, controlling the NCO content to 7.5%, and reacting at 90° C. for 2 h to obtain a prepolymer;
[0157] (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule and a disulfide to the prepolymer and continuing the reaction at 80°C for 1 hour;
[0158] (3) adding silane-modified EPDM rubber particles and nanofiller materials, stirring and dispersing them uniformly, and cooling to 70° C.; wherein the silane-modified EPDM rubber particles are prepared by the following steps: washing the EPDM rubber particles and drying them at 100° C. for 2 h, mixing γ-mercaptopropyl triethoxysilane and γ-aminopropyl triethoxysilane in proportion and stirring them for 2 min, adding the EPDM rubber particles to the mixed solution at 80° C. and stirring for reaction for 2 h, and drying them at 80° C. for 3 h after the reaction;
[0159] (4) adding 4,4'-diaminodicyclohexylmethane chain extender, dibutyltin dilaurate, triphenylphosphine, stabilizer and organosilicon enhancer, and stirring well to form a self-healing polyurethane elastomer material.
[0160] The self-healing polyurethane elastomer material prepared in Example 2 was subjected to performance testing, and the results obtained are shown in Table 20 below.
[0161] Table 20 Performance indicators of self-healing polyurethane elastomer materials of Example 2
[0162]
[0163]
[0164] It can be seen from Table 20 that the self-healing polyurethane elastomer material of Example 2 exhibits excellent comprehensive performance, with a tensile strength of 28MPa, an elongation at break of 684%, a shear strength of 19MPa, and a hardness of 74 (ShoreA), which meets the mechanical performance requirements under a variety of harsh environments. The healing efficiency of the material is remarkable. After fracture, the tensile strength and elongation at break at 70°C for 24 hours are restored to more than 85% and more than 90%, respectively, showing excellent self-healing ability. At the same time, the material has outstanding performance in corrosion resistance, aging resistance and wear resistance. There is no crack in the salt spray test for 1000 hours, the performance retention rate after ultraviolet aging is more than 97%, and only 30mg is lost in 5000 turns of wear. In addition, the material remains stable in high and low temperature cycles and water permeability tests, and the water permeability coefficient is 0mL / min, indicating that it has excellent stability and durability in harsh environments and is suitable for high-performance engineering needs.
[0165] (2) Self-healing polyurethane interface adhesive
[0166] The raw material components of the self-healing polyurethane interface adhesive of Example 2 are shown in Table 21. Among them, the component content of the acylhydrazone bond-containing functionalized small molecule is shown in Table 15.
[0167] Table 21 Component contents of self-healing polyurethane interface adhesive in Example 2
[0168] Serial number raw material Content / portion 1 Isophorone diisocyanate (IPDI) 40 2 Polycaprolactone diol (PCL) 33 3 4,4'-Diaminodicyclohexylmethane (PACM) chain extender 10 4 Acylhydrazone-functionalized small molecules 5.775 11 Multi-walled carbon nanotubes (MWCNTs) 1.5 12 γ-Aminopropyltriethoxysilane (KH550) 4 13 Dibutyltin dilaurate (DBTDL) 0.2 14 Silicone synergist 0.3 15 Light Stabilizer 944 0.1
[0169] The self-healing polyurethane interface adhesive of Example 2 is prepared by the following steps:
[0170] (1) heating polycaprolactone diol to 70° C., stirring and melting under nitrogen protection, adding isophorone diisocyanate, controlling the NCO content to 5%, and reacting at 90° C. for 3 hours to obtain a polyurethane prepolymer;
[0171] (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule to the prepolymer and continuing the reaction at 80°C for 1 hour;
[0172] (3) mixing carbon nanotubes and γ-aminopropyltriethoxysilane, and adding the mixture to the system of step (2) to uniformly disperse the mixture;
[0173] (4) adding 4,4'-diaminodicyclohexylmethane, dibutyltin dilaurate, an organosilicon enhancer and a light stabilizer, and stirring evenly at 70° C. to obtain a self-healing polyurethane interface adhesive material.
[0174] The self-healing polyurethane interface adhesive prepared in Example 2 was subjected to performance testing, and the results obtained are shown in Table 22 below.
[0175] Table 22 Performance indicators of self-healing polyurethane interface adhesive of Example 2
[0176] Test items Test Standards Test Results Steel bond strength ASTMD1002 13.6MPa Interfacial peel strength ASTMD1876 34N / mm Tensile strength(MPa) GB / T528-2009 21 Elongation at break (%) GB / T528-2009 554 Modulus (100% stretch) GB / T528-2009 4.8 Healing efficiency (shear strength) After breaking, place at 70℃ for 24 hours >84% recovery Healing efficiency (elongation) After breaking, place at 70℃ for 24 hours >89% recovery Operation time (minutes) 25℃, 50% humidity 22 Curing time (hours) Under the condition of 60℃ 2.1
[0177] As can be seen from Table 22, the self-healing polyurethane interface adhesive of Example 2 exhibits good performance, with a steel bonding strength of 13.6MPa and an interface bonding strength of 34N / mm, showing excellent interface bonding ability and peeling resistance. The tensile strength of the material is 21MPa, and the elongation at break is 554%, indicating that it has both high strength and good flexibility. The modulus (100% stretching) is 4.8MPa, providing suitable elastic stiffness. The healing efficiency is significant, and the shear strength and elongation at 70°C for 24 hours are restored to more than 84% and more than 89%, respectively, showing excellent self-healing properties. In addition, the operation time is 22 minutes and the curing time is only 2.1 hours, showing good construction convenience. These performance indicators show that the material has broad application prospects in the fields of expansion joint angle steel sealing, interface repair and high-performance bonding.
[0178] (3) Seamless telescopic structure
[0179] The seamless telescopic structure of this embodiment 1 includes a carbon fiber steel composite plate 2 arranged in an expansion joint slot 1, an outer angle steel 3 attached to both sides of the expansion joint slot 1, a self-healing polyurethane interface adhesive layer 4 coated on the inner side of the outer angle steel 3, an inner angle steel 7 arranged on the inner side of the outer angle steel 3 and forming an integral body with the outer angle steel 3, an elastic stabilizing element 5 (which can be a combination of a spring and a steel rod) laid layer by layer horizontally, and a self-healing polyurethane elastomer material layer 6 filled in the expansion joint slot 1.
[0180] The construction method of the seamless telescopic structure comprises the following steps:
[0181] (1) Use a dust-free cutting machine to evenly cut on both sides of the expansion joint to form a notch (e.g., 80 cm wide) and clean the notch to remove the slurry on the surface of the concrete cushion layer.
[0182] (2) Carbon fiber steel composite plates (for example, 15 mm thick and 40 cm wide) are laid out on both sides of the expansion joint with equal width, and fixed to the concrete beam with limit pins. After the carbon fiber steel composite plates are laid out, rubber sheets are laid on the steel plates to isolate the composite plates from direct contact with the elastomer;
[0183] (3) Install the outer angle steel. The highest point of the outer facade of the outer angle steel should be flush with the original asphalt pavement. The outer angle steel should be welded to the original expansion joint door-shaped steel bar with welding rods.
[0184] (4) Pour fast-setting C50 steel fiber concrete in the anchoring area and sprinkle water to cure for 12 hours after pouring.
[0185] (5) Apply self-healing polyurethane interface adhesive to the inner interface of the outer angle steel. The coating amount can be 0.5kg / m 2 .
[0186] (6) Pour the first layer of self-healing polyurethane elastomer with a thickness of 2 cm.
[0187] (7) Install the inner angle steel and fix it to the outer angle steel with bolts to form an integral whole. Pour the self-healing polyurethane concrete again with a thickness of 4.5 cm. Simultaneously install the elastic stabilizing elements at intervals of 15 cm and fix them in the holes of the inner angle steel with clips. Wait for initial curing for 1 hour.
[0188] (8) Pour the last layer of self-healing polyurethane elastomer with a thickness of about 0.5 cm, flush with the original asphalt pavement and anchoring concrete. Use a scraper to level it and allow it to cure. Traffic can be opened after 24 hours of curing.
[0189] The carbon fiber steel composite plate arranged above the bridge structure seam in the seamless telescopic structure is composed of a steel matrix layer and a carbon fiber reinforcement layer through an epoxy resin interface bonding layer. The steel matrix layer is 13-15 mm, the steel matrix is Q355B, the sandblasting rust removal grade is not less than Sa2.5, and the roughness is 80 μm; the epoxy resin interface bonding layer includes 100 parts of bisphenol A epoxy resin E44, 10 parts of active diluent AGE, 50 parts of m-phenylenediamine (m-PDA), 10 parts of terminal carboxyl liquid nitrile rubber (CTBN), and 3 parts of 7-15 nanometer silica thickener. The carbon fiber reinforcement layer is 3-5 layers of carbon fiber fabrics arranged alternately at 0° and 90°, vacuum hot pressed at 180°C and 2MPa for curing for 2h, and the thickness is 5mm.
[0190] The performance results of the carbon fiber steel composite plate are shown in Table 23 below.
[0191] Table 23 Performance results of carbon fiber steel composite plate
[0192] Test items Test Standards Test Results Tensile strength(MPa) GB / T6396-2008 1092 Bending strength(MPa) GB / T6396-2008 764 Shear strength(MPa) GB / T6396-2008 72.8 <![CDATA[Impact strength (kJ / m 2 )]]> GB / T6396-2008 54 Interface bonding strength (MPa) GB / T6396-2008 36 Fatigue life (high frequency alternating load) <![CDATA[±100MPa、50Hz、10 6 Cycle]]> No cracks or peeling Fatigue life (high and low temperature alternating environment) -20℃ to 60℃, 50 cycles No noticeable performance degradation
[0193] In addition, the seamless telescopic structure prepared by the present invention was subjected to performance testing, as follows:
[0194] The salt spray test (ASTM B117) showed that the device had no cracks or performance degradation after 1000 hours; the fatigue test (high frequency alternating load ±100MPa, 50Hz, 10 6The device has no cracks or peeling after 2 cycles. In addition, as a road crack repair material, the material's fatigue resistance after crack filling is restored to more than 85% of the initial level. The operation time is 22 minutes, and the construction is simple. In addition, the overall structure of the device has 0 water seepage under the conditions of water seepage test, and the self-healing polyurethane elastomer has 0 voids, which has a good sealing effect. The overall verification shows that the present invention significantly improves the reliability and economy of engineering structures and has a wide range of promotion value.
[0195] In addition to the above embodiments, it should be noted that the raw materials and components, as well as the preparation process and process parameters specified in the present invention can all achieve the technical effects claimed in the present invention, so they are not listed one by one.
Claims
1. A self-healing polyurethane elastomer material based on dynamic reversible covalent bonds, characterized in that: The raw materials are as follows, in parts by weight: 30-40 parts of diphenylmethane diisocyanate, 20-30 parts of fluorine-containing polyether polyol, 10-15 parts of polyethylene adipate glycol diol, 5-10 parts of 4,4'-diaminodicyclohexylmethane chain extender, 3-6 parts of dynamic reversible bond monomer containing acylhydrazone bond functionalized small molecules, 2-4 parts of disulfide, 10-20 parts of silane-modified EPDM rubber particles, 1.5-4.5 parts of nano-filler material, 1-2 parts of triphenyl phosphine, 0.1-0.3 parts of dibutyltin dilaurate, 0.1-0.2 parts of stabilizer and 0.2-0.5 parts of silicone synergist.
2. The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds according to claim 1, characterized in that: The fluorine-containing polyether polyol comprises the following raw materials by weight: 65-75 parts of perfluoropropylene oxide, 5-10 parts of tetrafluoroethylene-hexafluoropropylene copolymer, 10-20 parts of propylene carbonate, 3-7 parts of terminal hydroxyl polyethylene glycol, 0.01-0.05 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum and 0.01-0.03 parts of 2,6-di-tert-butyl-p-cresol.
3. The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds according to claim 1, characterized in that: The dynamic reversible bond monomer containing acylhydrazone bond functionalized small molecules comprises the following raw materials by weight: 10 to 20 parts of terephthaloyl hydrazide, 15 to 25 parts of isophthalic acid dialdehyde, 25 to 35 parts of polyethylene glycol, 15 to 25 parts of 1,4-butanediol, 1 to 3 parts of graphene oxide, 0.3 to 0.7 parts of glacial acetic acid catalyst and 10 to 15 parts of anhydrous ethanol.
4. The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds according to claim 1, characterized in that: The disulfide comprises the following raw materials by weight: 30-45 parts of dibenzoyl disulfide, 25-35 parts of diethyl disulfide, 15-25 parts of 3,3'-thiodipropionic acid and 8-13 parts of diphenylacetyl disulfide.
5. The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds according to claim 1, characterized in that: The silane-modified EPDM rubber particles include the following raw materials by weight: 85-90 parts of EPDM rubber particles, 3-5 parts of γ-mercaptopropyltriethoxysilane and 10-12 parts of γ-aminopropyltriethoxysilane.
6. The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds according to claim 1, characterized in that: The nano-filling material comprises the following raw materials by weight: 45-55 parts of graphene oxide and 55-45 parts of multi-walled carbon nanotubes.
7. The self-healing polyurethane elastomer material based on dynamic reversible covalent bonds according to claim 1, characterized in that: The stabilizer includes one or more of ultraviolet absorbers UV326, UV531 or UV328, light stabilizer 944 and antioxidant 1010.
8. A method for preparing the self-healing polyurethane elastomer material according to claim 1, characterized in that: The steps include: (1) heating the fluorine-containing polyether polyol and polyethylene adipate glycol diol to 70-80° C., stirring and mixing under nitrogen protection, adding diphenylmethane diisocyanate, controlling the NCO content to 7.0%-8.5%, and reacting at 80-90° C. for 2-3 hours to obtain a prepolymer; (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule and a disulfide to the prepolymer, and continuing the reaction at 70 to 80° C. for 1 to 2 hours; (3) adding silane-modified EPDM rubber particles and nanofiller materials, stirring and dispersing them uniformly, and cooling to 60-70° C.; (4) adding 4,4'-diaminodicyclohexylmethane chain extender, dibutyltin dilaurate, triphenylphosphine, stabilizer and organosilicon enhancer, and stirring well to form a self-healing polyurethane elastomer material.
9. A seamless telescopic structure, characterized in that: The structure includes a carbon fiber steel composite plate arranged in the expansion joint groove, an outer angle steel bonded to both sides of the expansion joint groove, a self-healing polyurethane interface adhesive layer coated on the inner side of the outer angle steel, an inner angle steel arranged on the inner side of the outer angle steel and forming an integral body with the outer angle steel, elastic stabilizing elements laid layer by layer horizontally, and a self-healing polyurethane elastomer material layer formed by the self-healing polyurethane elastomer material described in claim 1 and filled in the expansion joint groove.
10. The seamless telescopic structure according to claim 9, characterized in that: The raw materials used in the self-healing polyurethane interface adhesive layer include, by weight: 35-45 parts of isophorone diisocyanate, 25-35 parts of polycaprolactone diol, 5-10 parts of 4,4'-diaminodicyclohexylmethane chain extender, 3-7 parts of dynamic reversible bond monomer containing acylhydrazone bond functionalized small molecules, 1-3 parts of multi-walled carbon nanotubes, 2-4 parts of γ-aminopropyltriethoxysilane, 0.1-0.3 parts of dibutyltin dilaurate, 0.2-0.4 parts of organosilicon synergist and 0.1-0.2 parts of light stabilizer.
11. The seamless telescopic structure according to claim 10, characterized in that: The raw materials used in the self-healing polyurethane interface adhesive layer are prepared by the following steps: (1) heating polycaprolactone diol to 70-80° C., stirring and melting under nitrogen protection, adding isophorone diisocyanate, controlling the NCO content to 4.0-5.0%, and reacting at 80-90° C. for 2-3 hours to obtain a polyurethane prepolymer; (2) adding a dynamic reversible bond monomer containing an acylhydrazone bond functionalized small molecule to the prepolymer, and continuing the reaction at 70-80° C. for 1-2 hours; (3) mixing multi-walled carbon nanotubes and γ-aminopropyltriethoxysilane, and adding the mixture to the system of step (2) to uniformly disperse the mixture; (4) adding 4,4'-diaminodicyclohexylmethane, dibutyltin dilaurate, an organosilicon enhancer and a light stabilizer, and stirring evenly at 60-70° C. to obtain a self-healing polyurethane interface adhesive material.
12. The seamless telescopic structure according to claim 9, characterized in that: The carbon fiber steel composite plate comprises a steel matrix layer, an epoxy resin interface bonding layer located on the steel matrix layer, and a carbon fiber reinforcement layer located on the epoxy resin interface bonding layer; The raw materials used in the epoxy resin interface bonding layer include the following raw materials by weight: 100 parts of bisphenol A epoxy resin, 10-15 parts of active diluent, 50-60 parts of m-xylylenediamine, 10-20 parts of carboxyl-terminated liquid nitrile rubber and 3-5 parts of nano silicon dioxide; The carbon fiber reinforcement layer is 3 to 5 layers of carbon fiber fabrics arranged alternately at 0° and 90° directions.